Applying DEA sensitivity analysis to efficiency measurement of Vietnamese universities - Thi Thanh Huyen Nguyen; Gervais Thenet; Khac Minh Nguyen (Management Science Letters)
The primary purpose of this study is to measure the technical efficiency of 30 doctorate-granting universities, the universities or the higher education institutes with PhD training programs, in Vietnam, applying the sensitivity analysis of data envelopment analysis (DEA). The study uses eight sets of input-output specifications using the replacement as well as aggregation/disaggregation of variables. The measurement results allow us to examine the sensitivity of the efficiency of these universities with the sets of variables. The findings also show the impact of variables on their efficiency and its “sustainability”.